PAIN RELIEF IN NEUROPATHIC PAIN-A COMPARISON BETWEEN 0.5% BUPIVACAINE AND 0.5% BUPIVACAINE STREPTOMYCIN COMBINATION: Pain Relief in Neuropathic Pain - Akhtar, Farrukh Mahmood; Rehman, Muhammad Matloob ur; Ahmed, Mubashar; Akmal, Mohammad; Mushtaq, Saleem (Pakistan Armed Forces Medical Journal, 2016)
ABSTRACT Objective: To compare the effectiveness of a combination of streptomycin and bupivacaine for the management of neuropathic pain against bupivacaine alone. Study Design: A randomized controlled double blinded trial. Place and Duration of Study: Pain clinic Combined Military Hospital (CMH) Rawalpindi, CMH Nowshera, Dermatology Dept. Military Hospital (MH) Rawalpindi, Department of Medicine, Surgery CMH Nowshera Feb 2009 to Feb 2010. Material and Methods: Fifty patients with post herpetic neuralgia (PHN), 10 patients with trigeminal neuralgia and 20 patients with nerve entrapment pain were included in the study. For each type of neuropathic pain, the patients were randomly divided into two groups. Group (B) received nerve blocks using 0.5% bupivacaine and group (BS) received nerve blocks using 0.5% bupivacaine and streptomycin 1gm combination. A series of four nerve blocks on alternate days were given. VAS (Visual Analogue Scale) was recorded at four, eight and twelve weeks after the last nerve block. Mean baseline VAS and at 12 weeks post treatment in groups B and BS were compared for pain relief and the mean VAS at 12 week post treatment in both the groups was compared for the difference in pain relief between the two groups. Students’t test was used for statistical analysis utilizing SPSS 10 versions. Results: Post herpetic neuralgia - group (B): at 12 weeks, mean VAS was 5.75 in gp (B) and 2.26 in gp (BS) respectively. Nerve entrapment pain- group (B): at 12 weeks, mean VAS was 6.62 whereas in group (BS) VAS was 1.33. Trigeminal neuralgia-group (B) At 12 weeks mean VAS was 7.0. gp (BS) mean VAS was 1. Pain relief achieved was excellent. Conclusion: Streptomycin and bupivacaine combination is an effective modality to manage neuropathic pain. The pain relief achieved by streptomycin–bupivacaine combination is superior to that achieved with bupivacaine alone.